Financing the development of artificial intelligence maid: an analysis of pertinent fiqhi issues - Sitiris, Miszairi; Busari, Saheed Abdullahi; Md. Sawari, Mohd. Fuad; Zaim, Muntaha Artalim (USIM, 2023)
Artificial Intelligence (AI) is the latest machine technology that is replacing the effort of humans and is the fastest-growing sector across the globe. The underlying ethos of AI is to create a secure ecosystem for every human endeavour. Investors are claiming that the invention of an AI assistant such as a robot maid is the future reality. The AI robot is unstoppable and will obstruct how things are done at home. The development of AI and the demand for it indicates a future challenge to domestic activities. Since technology is replacing human efforts, scholars and researchers are concerned about the permissibility of Islamic banks to finance AI projects for the development of robot-maid. A robot maid is likely to exploit gender issues simply because consumers might prefer an AI maid that is male or female. Social violation in the use of AI maid will likely trigger further queries. This study uses the doctrinal approach of the qualitative method to explore Islamic thresholds and analyzes the juristic consideration for financing the development of AI for human development. The study explains the understanding of AI, its contributions to the world economy, and some pertinent issues and challenges. This study found that the growth of AI interventions in homes and care services is a reality, but financing AI maids requires adherence to Islamic requirements, including Shariah compliance and consideration of ethical, economic, security, and social concerns.